Assessment of BIV1-CovIran inactivated vaccine–elicited neutralizing antibody against the emerging SARS-CoV-2 variants of concern. (June 2022) - Salehi, Mohammadreza; Hosseini, Hamed; Jamshidi, Hamid Reza; Jalili, Hasan; Tabarsi, Payam; Mohraz, Minoo; Karimi, Hesam; Lotfinia, Majid; Aalizadeh, Reza; Mohammadi, Mehrdad; Ramazi, Shahin; Abdoli, Asghar
Abstract: Objectives: The BIV1-CovIran vaccine is highly effective against COVID-19. The neutralizing potency of all SARS-CoV-2 vaccines seems to be decreased against variants of concern. We assessed the sensitivity of the Alpha (B.1.1.7), Beta (B.1.351), and Delta (B.1.617.2) variants to neutralizing antibodies (NAbs) present in sera from individuals who had received the BIV1-CovIran candidate vaccine compared with an original Wuhan-related strain. Methods: The ability of vaccine serum to neutralize the variants was measured using the conventional virus neutralization test. The correlation of spike (S) protein antibody and anti-receptor binding domain with neutralizing activity was investigated. Results: The current study demonstrated that 29 of 32 (90.6%; 95% CI: 75.0–98.0) of the vaccinees developed NAbs against a Wuhan-related strain. It is noteworthy that 28 (87.50%) and 24 of 32 (75%) of the recipients were able to produce NAbs against Alpha, Beta, and Delta variants, respectively. Serum virus-neutralizing titres for different SARS-CoV-2 strains were weakly correlated with anti–receptor binding domain antibodies (Spearman r = 36-42, p < 0.05), but not S-binding antibodies (p > 0.05). Discussion: Although there was a reduction in neutralization titres against the Alpha, Beta, and Delta variants compared with the Wuhan strain, BIV1-CovIran still exhibited potent neutralizing activity against the SARS-CoV-2 variants of concern. Graphical abstract: Image 1